2016
DOI: 10.1111/nmo.12952
|View full text |Cite
|
Sign up to set email alerts
|

May cannabinoids prevent the development of chemotherapy‐induced diarrhea and intestinal mucositis? Experimental study in the rat

Abstract: Background The antineoplastic drug 5‐fluoruracil (5‐FU) is a pirimidine analog, which frequently induces potentially fatal diarrhea and mucositis. Cannabinoids reduce gastrointestinal motility and secretion and might prevent 5‐FU‐induced gut adverse effects. Here, we asked whether cannabinoids may prevent diarrhea and mucositis induced by 5‐FU in the rat. Methods Male Wistar rats received vehicle or the non‐selective cannabinoid agonist WIN 55,212‐2 (WIN; 0.5 mg kg−1 injection−1, 1 injection day−1, 4 consecuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 60 publications
1
23
0
Order By: Relevance
“…Taranabant increased the number of bowel movements after systemic and oral administration and significantly increased fecal pellet output in mice with constipation induced by ipratropium (Fichna et al, 2013). It has been demonstrated that a low dose of a non-selective cannabinoid agonist WIN55,212-2 reduced the severity of 5-fluorouracil-induced diarrhea in rats (Abalo et al, 2016). …”
Section: Emerging and Potential Treatments For Cid And Cicmentioning
confidence: 99%
“…Taranabant increased the number of bowel movements after systemic and oral administration and significantly increased fecal pellet output in mice with constipation induced by ipratropium (Fichna et al, 2013). It has been demonstrated that a low dose of a non-selective cannabinoid agonist WIN55,212-2 reduced the severity of 5-fluorouracil-induced diarrhea in rats (Abalo et al, 2016). …”
Section: Emerging and Potential Treatments For Cid And Cicmentioning
confidence: 99%
“…Interestingly, using radiographic methods in rats, Vera et al showed that a CB1 receptor cannabinoid antagonist prevented the effect of acute vincristine on gastrointestinal motility, particularly in the small intestine. Thus, inactivation of the cannabinoid system might be useful to counteract CIC, whilst cannabinoid receptor activation might be used to counteract CID (Abalo et al, 2017 ; McQuade et al ).…”
Section: Introductionmentioning
confidence: 99%
“…As we have discussed above, the genesis of chemotherapy induced diarrhea is believed a complicated process resulting from combination and interaction of multiple factors including gene mutation and enzyme deficiency, intestinal mucosa inflammation, dysbacteriosis as well as nervous system disability. However, there are still puzzles and questions in all of the possible mechanisms [33][34][35][36][37]. Medications towards these mechanisms still cannot work very well in quite a number of cases.…”
Section: Enteric Nervous System Damagementioning
confidence: 99%